Effects of Chemical State of the Pd Species on H2 Sensing Characteristics of PdOx/SnO2 Based Chemiresistive Sensors - Tianjiao Qi; Jie Sun; Xi Yang; Fanfan Yan; Ji Zuo (Sensors, 2019)
In this paper, the PdOx nanoparticles modified SnO2 are prepared using sputtering and wet chemical methods. The SnO2 nanoparticles are separately added to a concentration of 0.75% to 10% PdCl2 to obtain a PdCl2/SnO2 composite material, which is calcined for 1 to 2 h at the temperatures of 120 °C, 250 °C, 450 °C and 600 °C. The PdOx/SnO2 nanocomposite was characterized by X-ray photoelectron spectroscopy (XPS), X-ray diffractometry (XRD) and transmission electron microscopy (TEM). Microstructural observations revealed PdOx with different chemical states attached to the surface of SnO2. Hydrogen response change tests were performed on the obtained PdOx/SnO2 gas sensing materials. The results show that the high gas sensing performance may be attributed to the contribution of the PdOx-loaded SnO2. In hydrogen, the best sensitivity response was attained at 80 °C, which is 60 times that of pristine SnO2. It clarifies the role of PdOx in the gas sensing mechanisms.